2006
DOI: 10.4049/jimmunol.177.9.5852
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Foxp3+CD4+CD25+ and IL-10-Secreting CD4+CD25+ T Cells during Cure of Colitis

Abstract: CD4+CD25+ regulatory T cells can prevent and resolve intestinal inflammation in the murine T cell transfer model of colitis. Using Foxp3 as a marker of regulatory T cell activity, we now provide a comprehensive analysis of the in vivo distribution of Foxp3+CD4+CD25+ cells in wild-type mice, and during cure of experimental colitis. In both cases, Foxp3+CD4+CD25+ cells were found to accumulate in the colon and secondary lymphoid organs. Importantly, Foxp3+ cells were present at increased density in colon samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
341
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(369 citation statements)
references
References 48 publications
25
341
1
2
Order By: Relevance
“…IL-10 is one of the best-known cytokines endowed with immune-suppressive functions. Il10 gene expression characterizes Treg-cell signature [30], even though a significant IL-10 expression at the protein level can be detected in naïve mice only in the intestine [15,31]. Treg-cellderived IL-10 is redundant for the control of systemic autoimmunity but becomes crucial for the control of inflammation at the mucosal interfaces with the external environment, such as in lungs and colon [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10 is one of the best-known cytokines endowed with immune-suppressive functions. Il10 gene expression characterizes Treg-cell signature [30], even though a significant IL-10 expression at the protein level can be detected in naïve mice only in the intestine [15,31]. Treg-cellderived IL-10 is redundant for the control of systemic autoimmunity but becomes crucial for the control of inflammation at the mucosal interfaces with the external environment, such as in lungs and colon [32].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells secrete interleukin 10 (IL-10), which plays a critical role in suppressing immune responses and in particular the maturation of fully competent DCs [13][14][15]. Among tumor-infiltrating Teff cells, the subpopulation of effector memory T (Tem) cells is the most abundant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it cannot be excluded that Tr1 cells require FOXP3 to exert their suppression in vivo. Indeed, in a preclinical model of inflammatory bowel disease, Treg expressing FOXP3 and secreting IL-10 are selectively localized in the intestinal lamina propria where they suppress Teff cells responses [32]. The origin of these cells is not clear.…”
Section: Foxp3 and Adaptive T Regulatory Type 1 (Tr1) Cellsmentioning
confidence: 99%
“…5,6 Pioneering experiments by Powrie et al demonstrated, more than 15 years ago, that transfer of naive CD4 + T cells into immunodeficient mice in the absence of Treg cells results in colitis that is dependent on the presence of commensal bacteria. [7][8][9] Remarkably, adoptive transfer of Treg cells not only prevents disease, but also, acting through both IL-10 and transforming growth factor-b (TGF-b)-dependent and -independent mechanisms, halts the progression of established disease and reverses pathology.…”
Section: M M U N O L O G Y R E V I E W a R T I C L Ementioning
confidence: 99%